The development of creative oral production based on poetry in preschool - Ortiz Mejia, Jenny; Cárdenas Figueroa, Ginna del Pilar; Niño Velásquez, Maribel (Rastros Rostros, 2024)
This article is based on the research project carried out at the La Victoria concentration with preschool children under the direction of the teacher Teresa Bohórquez, which deals with the development of poetic creativity through different strategies and activities within a Pedagogical Project.